Study Of Rice Husk Ash (RHA)-Based Sorbents For Simultaneous Removal Of Sulfur Dioxide (S02) And Nitrogen Oxides (Nox) From Flue Gas. - Lee, Keat Teong; Mohamed, Abdul Rahman; Harun @ Kamaruddin, Azlina (Universiti Sains Malaysia, 2008)

(untitled)
Adsorbents for dry-type flue gas desulfurization (FGD) were prepared from rice husk ash (RHA), calcium oxide and NaOH as additive by water hydration method. Two types of RHA were used in the experiment, one was obtained directly from the mill (black colored), and the other was obtained after pre-treatment of the black colored RHA with temperature at 600°C.